Gastric Carcinoma with Osteoclast-Like Giant Cells Coexisting with Gastrointestinal Spindle Cell Tumor - Christos Poulios; Triantafyllia Koletsa; Antonis Goulas; Georgia Karayannopoulou; Eleni Vrettou; Ioannis Kostopoulos (Case Reports in Pathology)
Reactive multinucleated osteoclast-like giant cells (OGCs) have been described in a variety of neoplasms but rarely in gastric carcinomas. Reported herein is a case of an 81-year-old Caucasian male presented with upper abdominal pain and dysphagia. Esophagogastroscopy revealed an ulcerative mass and a specimen of subtotal gastrectomy and lower esophagectomy was sent for histologic examination. At the gastroesophageal junction an exophytic tumor, measured 2.2 cm in greatest diameter, was observed. Sections from the tumor showed gastric adenocarcinoma, stage pT1bpN0. Diffusely among the neoplastic cells multinucleated giant cells, resembling osteoclasts, were observed, which were positive for CD68, lysozyme, and vimentin and negative for AE1/AE3, CK8/18, hHCG, and LMP1. Moreover, in a random section from the gastric fundus, a spindle cell lesion, sized 0.6 cm, was revealed, which was positive for CD117 and CD34 antigens and was diagnosed as gastrointestinal stromal tumor (GIST). The presence of OGCs is an uncommon finding in gastric carcinomas and by analogy to breast and pancreatic carcinomas it could characterize a rare distinct morphological variant of gastric adenocarcinoma. Due to the limited number of the reported cases, the prognostic value of OGCs is under discussion. Furthermore, pathologists should be aware that incidental GIST may accompany any tumor.